The functional form of yield curves - Vincent Brousseau (European Central Bank (ECB), 2002)
Yield curves built from liquid instruments tend to exhibit specific features, both in term of smoothness and in term of patterns. The paper presents empirical evidence that those liquid yiled curves frequently conform to a specific functional form. This specific functional form is predicted by a particular arbitrage pricing model. The paper also examines the possible interpretations of this phenomenon.
Keywords: G10; G12; G13; 330